Asplenic patients and invasive pneumococcal disease—how bad is it these days?. (October 2016) - Marrie, Thomas J.; Tyrrell, Gregory J.; Majumdar, Sumit R.; Eurich, Dean T.
Highlights: Consecutive patients ( n  = 2435) with invasive pneumococcal disease (IPD) were collected prospectively; 37 (1.5%) were asplenic. Asplenic patients had a more severe infection (e.g., need for mechanical ventilation, intensive care unit admission) and more complications (e.g., meningitis, acute kidney injury). However, the in-hospital mortality rate of 19% for those without a spleen was not significantly higher than that of 16% for those who had a spleen. Pneumococcal serotype 22B accounted for 27% of the isolates amongst the asplenic patients and this was 33-fold higher than the rate in the patients with a spleen. Summary: Objectives: Most are aware of pneumococcal infection as a complication of splenectomy and the increased risk of severe invasive pneumococcal disease (IPD) in asplenic patients. However little is known of the current status of this entity in a population with an active pneumococcal conjugate vaccine program for children. Methods: All IPD cases reported from 2000 to 2014 in Northern Alberta, Canada were collected prospectively. Socio-demographic variables, clinical characteristics, and IPD-related outcomes were compared between patients with and without a spleen using the Student t -test, Chi-square test, or Fisher's exact test, as appropriate. Results: Thirty-seven of 2435 patients with IPD (1.5%) were asplenic. Asplenic patients were significantly more likely to require mechanical ventilation or admission to the intensive care unit and had more complications (e.g., acute kidney injury). However, in-hospital mortality rates were similar in those with and without a spleen (19% vs. 16%, p  = 0.58). Pneumococcal serotype 22B was 33-fold higher in asplenic patients compared to those with a spleen. Conclusions: In patients with IPD, those who are asplenic have a more severe infection than those with a spleen; however, the mortality rate is not significantly different. The reason for the predominance of serotype 22B requires further investigation and if replicated may warrant attention to current vaccination strategies.